Effect of doping concentration for the properties of Fe doped TiO2 thin films applications. (2021) - Rajeswari, R.; Venugopal, D.; Dhayal Raj, A.; Arumugam, J.; John Sundaram, S.; Kaviyarasu, K.
Abstract: This paper reports the sol–gel preparation and subsequent characterization of Fe doped TiO2 thin films with different doping concentrations (1%, 3% and 5%). X-Ray Diffraction (XRD), Scanning Electron Microscopy (SEM), Energy Dispersive X-Ray analysis (EDX), UV–Visible analysis and Photoluminescence spectra analysis (PL) were used to characterize the prepared samples. The crystallite size of anatase phase increases from 4.76 nm to 7.61 nm when doping concentration increases from 1% to 3% and the anatase phase is transformed to brookite at the doping of 5% as the crystallite size of more than 14.82 nm. The surface morphological pictures are observing to be almost smooth and particle size dispensation of Fe doped titanium dioxide particles is non-spherical agglomeration crystallite formation. An optical band gap of 3.63 eV, 3.41 eV and 3.11 eV were obtained for the TiO2 thin films doped with 1%, 3% and 5% Fe respectively. PL analysis results the emission peaks at 347 nm for 1% Fe doped sample seems to shift slightly towards higher wavelength for 3% and 5% Fe doped samples. This may be due to reduction in bandgap because of the shallow trap state created near the absorption band edge as a result of doping.